2001
DOI: 10.1097/00000374-200107000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Daily Ethanol and Withdrawal: 2. Behavioral Changes During Prolonged Abstinence

Abstract: These results suggest that repetitive daily alcohol consumption and withdrawal can induce not only persistent defects in HPA function, but also persistent increases in anxiety and behavioral responsiveness to novelty, all consistent with characteristics of abstinent alcoholics as well as with rats that self-administer increased amounts of alcohol and other drugs of abuse. This suggests that alcohol abuse can induce persistent common or interacting changes in neuroendocrine and behavioral responses that may inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
2
40
0
2
Order By: Relevance
“…Ethanol fed rats showed a significant reduction in basic and fine movement, X and Y ambulation, the number of entries produced in the closed arms of the elevated plus maze and the number of lines crossed in the open field compared to control rats. This ethanol withdrawal induced hypolocomotion following chronic ethanol exposure is synonymous with some previous studies [40,41] and withdrawal induced hypoactivity is an additional behavioural sign of ethanol withdrawal [12]. MPEP at 2.5 and 5 mg/kg significantly decreased basic movement, fine movement, X ambulation, and Y ambulation in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 78%
“…Ethanol fed rats showed a significant reduction in basic and fine movement, X and Y ambulation, the number of entries produced in the closed arms of the elevated plus maze and the number of lines crossed in the open field compared to control rats. This ethanol withdrawal induced hypolocomotion following chronic ethanol exposure is synonymous with some previous studies [40,41] and withdrawal induced hypoactivity is an additional behavioural sign of ethanol withdrawal [12]. MPEP at 2.5 and 5 mg/kg significantly decreased basic movement, fine movement, X ambulation, and Y ambulation in the elevated plus maze.…”
Section: Discussionsupporting
confidence: 78%
“…This test is one of the most popular animal tests of anxiety currently in use. Although it has been frequently used as a tool to screen anxioselective effects of drugs (Handley and Mithani 1984;Pellow et al 1985;Pellow and File 1986), nowadays its usefulness has spread towards the understanding of the biological basis of emotionality (Adamec et al 1998;Carobrez et al 2001;Lamprea et al 2000;Rasmussen et al 2001). It has been suggested that the social interaction and the elevated plus-maze tests measure distinct facets of anxiety (i.e., social anxiety in the social interaction test and generalized anxiety in the elevated plus-maze test) that may be differentially susceptible to drug treatments (File and Hyde 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in animal studies of ethanol withdrawal, anxiety is seen as a prominent withdrawal symptom (File et al 1989(File et al , 1991Costall et al 1990;Lal et al 1991;Moy et al 1997;Gatch et al 1999Gatch et al , 2000Jung et al 2000;Kampov-Polevoy et al 2000;Rasmussen et al 2001). Again, most of these studies of withdrawal anxiety have used either ethanol injection or a forced ethanol diet as opposed to free selfadministration of ethanol.…”
Section: Introductionmentioning
confidence: 99%